2022
DOI: 10.1016/j.aninu.2021.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Different copper sources and levels affect growth performance, copper content, carcass characteristics, intestinal microorganism and metabolism of finishing pigs

Abstract: Copper (Cu) is an essential trace element in the production of swine. This study was conducted to investigate the effect of 3 different sources of Cu on growth performance, Cu metabolism, and intestinal microorganisms of finishing pigs, so as to estimate the bioavailability of the 3 sources for pigs. A total of 42 male finishing pigs (88.74 ± 5.74 kg) were randomly allocated to 7 treatments. The factors were 3 sources (CuSO 4 , Cu-glycine, Cu-proteinate) and 2 levels (5 and 20 mg/kg) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…It has been established previously that weaned pigs fed an organic Cu source showed greater gain and feed efficiency compared with that pigs fed an inorganic Cu source [ 3 , 5 , 6 ]. Furthermore, although Zhao et al [ 3 ] reported that a relatively lower organic Cu (CuHMB) source increases the ADG and carcass weight of finishing pigs compared with that in pigs fed inorganic Cu source [ 3 ], others have reported that the Cu source did not affect weight gain during the growing and finishing phases [ 4 , 7 ]. Overall, both organic and inorganic Cu sources may have positive effects on growth performance in the overall growth stage of pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established previously that weaned pigs fed an organic Cu source showed greater gain and feed efficiency compared with that pigs fed an inorganic Cu source [ 3 , 5 , 6 ]. Furthermore, although Zhao et al [ 3 ] reported that a relatively lower organic Cu (CuHMB) source increases the ADG and carcass weight of finishing pigs compared with that in pigs fed inorganic Cu source [ 3 ], others have reported that the Cu source did not affect weight gain during the growing and finishing phases [ 4 , 7 ]. Overall, both organic and inorganic Cu sources may have positive effects on growth performance in the overall growth stage of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In the body, Cu is mainly stored in the liver and kidneys, and the Cu content in these organs contributes to the Cu concentration in the blood [ 19 ]. It has been reported that liver Cu concentration is high in pigs fed a Cu-rich diet, and excessive Cu accumulation can lead to its leakage into the circulatory system [ 4 , 12 ]. The blood Cu concentrations in weaned and finishing pigs are reported to have increased after the intake of dietary Cu [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different Cu sources also affect the bioavailability in livestock diets. Several studies have demonstrated that organic Cu, such as Cu–glycine and Cu–proteinate, has greater bioavailability compared to inorganic Cu; , for example, Wen et al reported that organic Cu provides benefits to intestinal microbiota and reduces Cu excretion in pigs compared with inorganic Cu. Li et al also found that organic Cu is less toxic and has a higher absorption efficiency compared with inorganic Cu.…”
Section: Copper and Livestockmentioning
confidence: 99%
“…High Cu improves the environmental adaptability of soil microorganisms and induces toxicity in agricultural soils . A study also indicated that high-Cu diets can alter the gut microenvironment and impact the composition and abundance of bacteria in livestock; for example, dietary high Cu decreases the intestinal microbial diversity but increases the ratio of Firmicutes to Bacteroidetes in pigs . Dietary Cu also enhances ruminal microbial fermentation in ruminants .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation